2019
DOI: 10.1111/corg.12300
|View full text |Cite
|
Sign up to set email alerts
|

How do board ties affect the adoption of new practices? The effects of managerial interest and hierarchical power

Abstract: Research Question/Issues Most extant literature implicitly equates obtaining information through board interlocks to acting on the information. We investigate triggers that help to translate the information into action. In addition to exposure to the information by board interlocks, we suggest that the self‐interest of the individuals who create these ties and hierarchical power of interlinked firms determines the likelihood of taking actions of adopting new practices. Research Findings/Insights Using the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Our focus on global corporate governance matters is evident by the breadth of contexts investigated by the 23 articles published in 2020. For example, in Issue 1, Yoshikawa et al (2020) study changes to the Japanese corporate governance framework to investigate whether information gained through board ties is translated into specific action. They find that the adoption of new corporate governance practices in interlinked firms depends on the self-interests of the directors with interlocking ties as well as the hierarchical power of interlinked firms.…”
Section: Highlights Of Articles Published In Volume 28mentioning
confidence: 99%
“…Our focus on global corporate governance matters is evident by the breadth of contexts investigated by the 23 articles published in 2020. For example, in Issue 1, Yoshikawa et al (2020) study changes to the Japanese corporate governance framework to investigate whether information gained through board ties is translated into specific action. They find that the adoption of new corporate governance practices in interlinked firms depends on the self-interests of the directors with interlocking ties as well as the hierarchical power of interlinked firms.…”
Section: Highlights Of Articles Published In Volume 28mentioning
confidence: 99%
“…At the network-level, homophily may limit the information that firms choose to share, limiting the diffusion of relevant knowledge. For example, if conservative boards are more likely to encourage adoption of governance practices, and liberal boards of CSR, among interlocked firms (as postulated by Gupta & Wowak, 2017), network homophily may inhibit the spread of best practices-a key benefit of interlock networks (Yoshikawa et al, 2019).…”
Section: Robustness Checksmentioning
confidence: 99%
“…The board of directors is the “apex of decision control” (Fama & Jensen, 1983, p. 311), setting the strategic direction and objectives of the firm (Bailey & Peck, 2013). Board interlocks—formed when a director serves on the board of two firms (Mizruchi, 1996)—are a key conduit of information for boards' decision making, providing access to market intelligence (Yoshikawa et al, 2019), aiding in the diffusion of new and best practices (Beckman & Haunschild, 2002), and opening access to critical resources (Withers et al, 2012). Consequently, the composition of the board and the firm's position within interlock networks are pertinent topics in organizational research for two reasons: (1) Interlocks affect the volume and content of interfirm information flows (Li, 2019; Yoshikawa et al, 2019), and (2) the cognitive frameworks of directors influence how this information is used in decisions (Bailey & Peck, 2013; van Ees et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations can use board interlocks as a way to create links with their dependent sources and to reduce uncertainty. Board ties to other firms provide a unique opportunity for directors to exchange information, to observe the business practices of their peers, create new business opportunities, and to obtain general business information [1,8,9]. Thus, research has shown that corporate practices that are shared among firms via board interlocks tend to have an impact on the dissemination of innovation [10][11][12][13], diversification strategies [4], the adoption of golden parachutes and social corporate responsibility practices [14], stock options and poison pills [15,16], as well as the creation of joint ventures [17] and the adoption of multidivisional organization forms [18].…”
Section: Introductionmentioning
confidence: 99%